(untitled) (Research, Society and Development, 2023)
Dyslipidemias are multifactorial diseases that can be diagnosed by measuring the plasma concentrations of lipoproteins important for both cholesterol and triglyceride transport. Cholesterol is a complex lipid-steroid compound mainly found in animal fats and plays multiple functions in the body. Statins are a class of medications that inhibit the enzyme HMG-CoA reductase, and by reducing cholesterol production, they increase the expression of low-density lipoprotein (LDL) receptors, which can help lower blood cholesterol levels and reduce the risk of heart disease. They are the most prescribed medications to treat dyslipidemia and lower cholesterol levels. The objective of this study is to present the benefits of dyslipidemia treatment using statins and discuss their main effects on the body. This is a systematic literature review where articles were selected using ScieLo, PubMed, and Google Scholar platforms, and only articles published from the year 2018 onwards were chosen for the research sample. It was observed that the use of statins can be considered an appropriate choice despite some health risks associated with their use. It is concluded that the use of statins in the treatment of dyslipidemia is effective and safe due to the reduction in blood cholesterol levels, inhibition of the HMG-CoA enzyme conversion, and improvement of patients’ lipid profiles. It is important to assess each patient individually to determine the best treatment option.